Characteristics of second primary malignancies following bispecific antibodies therapy - Dan Liu; Tong Li; Liang Wang; Jia Guo; Xinyu Zhou; Hongsheng Zhou; Xiaojie Liang; Baiwei Luo; Bingyu Lin; WeiXiang Lu; Shengyu Tian; Zihong Cai; et al. (Journal for ImmunoTherapy of Cancer)
Background The risk of secondary primary malignancies (SPMs) associated with bispecific antibody (BsAb)—a promising alternative to chimeric antigen receptor (CAR)-T therapy—remains insufficiently explored.Methods Using large-scale, real-world data from the US Food and Drug Administration’s Adverse Event Reporting System, we identified the relative frequency and characteristics of SPMs following BsAbs therapy and conducted a comprehensive comparison of treatment-related SPM profiles between BsAbs and CAR-T therapies.Results We identified 108 cases among 10,280 BsAb-treated patients. The incidence risk of SPMs was stable over the past 8 years, accounting for 1–2% of all adverse events, with a case fatality rate of 29.63% among the SPM cases. Myeloid leukemias and non-Hodgkin’s lymphoma were more frequent in blinatumomab recipients, while solid malignancies predominated in those treated with teclistamab. Time-to-onset (TTO) was significantly shorter in BsAb recipients compared with non-recipients, with weight and treatment duration influencing TTO, while no significant differences in TTO were observed across different BsAb products, ages, and genders. Our findings highlight the first year of BsAbs as a critical window for early detection and intervention. Although the overall risk of SPMs was lower with BsAbs than with CAR-T, the outcomes of SPMs were comparable in both groups. TTO and SPM patterns were statistically similar between the two therapies.Conclusion Our study provides the first detailed characterization of SPMs post-BsAb, underscoring the need for continued pharmacovigilance and individualized risk management to mitigate SPM risks in patients undergoing BsAb therapy.